Deteksi Dini Penyakit Akibat Kerja Impak Paparan Debu PM 10 Dan PM2,5 Di Home Industri Meubel Dengan Oksimeter - Agus Sutopo; Wibowo Ady Sapta; Bambang Murwanto; Helina Helmy (STIKES Columbia Asia Medan, 2025)
Home industries are small- to medium-scale production units operated within or near households, typically relying on family members or a limited local workforce, with modest capital and without large-scale industrial technology. In furniture production, the main outputs are household items such as chairs, tables, wardrobes, beds, and shelves, while by-products include sawdust and unused wood pieces. Airborne pollutants— particularly wood dust (PM₁₀ and PM₂.₅) from sanding and cutting, along with fumes from paints, solvents, and adhesives—pose significant short- and long-term health risks to workers. This community service project, in collaboration with higher education institutions, aimed to establish long-term control measures. Initial steps involved measuring PM₁₀ and PM₂.₅ concentrations and assessing workers’ blood oxygen levels. Using a descriptive approach, workplace conditions were compared before and after work. Findings revealed a correlation between dust levels and blood oxygen saturation, supporting recommendations for long-term occupational health interventions.